(untitled) (Journal of Laboratory Animal Science, 2024)
Studies were aimed to evaluate the phytochemical composition of the Sapindus laurifolius leaves and toxicological effect of the Sapindus laurifolius leaf extract using Wistar albino rats as a model animal. The phytochemical analysis was performed using High Performance Thin Layer Chromatography (HPTLC). In toxicity studies, the acute oral toxicity study was conducted as per the guidelines of Organization for Economic Co-operation and Development (OECD 423 Acute Toxic Class Method) for testing of chemicals. In repeated dose 28-day oral toxicity study (OECD 407), leaf extract administered at the dose of 50, 200 and 800 mg/kg and limit dose of 1000 mg/kg. The phytochemical analysis revealed the presence of saponins, flavanoids, glycosides and bitter principles. In acute toxicity study, the LD50 cut-off values were found to be more than 2g/kg in leaf extract. In repeated dose 28-day oral toxicity, significant (P<0.05) increase in AST, ALT, BUN and creatinine, significant (P<0.05) increase in total protein was noticed. The histopathological changes confined to liver, kidney and intestine, revealed mild to moderate hepatotoxicity, severe nephrotoxicity and increased goblet cell activity. The changes were found to correlate with increased dose of leaf extract. Thus the phytochemical analysis of S. laurifolius revealed the presence of saponins, glycosides, flavonoids and bitter principles.The acute oral toxicity study of S. laurifolius methanolic leaf extract in rats resulted in no toxicity even at the highest dose, in repeated 28- day oral toxicity study revealed mild to moderate hepatotoxicity, severe nephrotoxicity and intestinal damage.